Pembuatan Dan Pengujian Mesin Bending Rotary Baja Untuk Aplikasi Stand Pot Bunga Diameter 8 dan 10 Inch - Ruzita Sumiati; Genta Ramadeto; Rakiman Rakiman; Fardinal Fardinal (Politeknik Negeri Padang, 2020)
In this day and age people decorate homes with flower pots and many models of flower pot place creations. Usually the place to put flower pots in the form of a circle and to make a circular iron is made manually requires energy and a long time. A bending machine is needed to make concrete iron circle creations. The aim of this research is to produce a rotary bending machine that is able to work efficiently in forming a concrete steel circle. The method used in this study is a practical method that is doing machine design and continued with the manufacture and field testing. The working principle of this machine is to use a motor that functions to move the Gearbox and continue the rotation to the shaft, then the shaft rotates and the bending mall rotates and makes the steel concrete come round and circular. The conclusion is (a). This concrete steel rotary bending machine has dimensions of 550 mm x 550 mm x 1000 mm with an electric motor drive power source (b). The results of the bending process using a concrete steel rotary bending machine are far more efficient than doing manual bending